2021
DOI: 10.3846/jbem.2021.15601
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Relationship Between Integrated Reporting Quality and Sustainable Business Development

Abstract: The aim of the paper is to provide an overview of the sensitivity in terms of the preference for using the integrated reporting quality (IRQ) based on the reporting companies’ field of activity. The study focusses on designing a sensitivity analysis relying on the most relevant financial and nonfinancial indicators as required by the stakeholders. They were adjusted by the key factors for the IRQ such as the social, natural, human and intellectual capital. The study has been designed based on the upgrade and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…According to them, current high-quality integrated reports do not appear to improve a company's information environment and do not provide additional relevant information to capital markets in a voluntary setting. Cosmulese et al (2019), Matemane and Wentzel (2019) and Ciubotariu et al (2021) examined the relationship between IR quality and financial performance and found that only earnings per share were positively related, while firm value and profitability were not associated. Future research needs to reexamine this issue, considering that short-term earnings represented by EPS are as important as long-term values represented by Tobin's Q and economic value added.…”
Section: Consequencesmentioning
confidence: 99%
“…According to them, current high-quality integrated reports do not appear to improve a company's information environment and do not provide additional relevant information to capital markets in a voluntary setting. Cosmulese et al (2019), Matemane and Wentzel (2019) and Ciubotariu et al (2021) examined the relationship between IR quality and financial performance and found that only earnings per share were positively related, while firm value and profitability were not associated. Future research needs to reexamine this issue, considering that short-term earnings represented by EPS are as important as long-term values represented by Tobin's Q and economic value added.…”
Section: Consequencesmentioning
confidence: 99%
“…No doubt that investors will be highly interested in the renewable energy costs and in the way they will affect their profits, yet, at the same time, the concern for ensuring the sustainability of their investments will become a top priority when it comes to the protection of the environment and to setting in place of the organisational policies which will show the community their best intentions (Socoliuc et al, 2018;Socoliuc et al, 2020;Ciubotariu et al, 2021). Consequently, the findings of this paper reinforce the ideea that the investments in the renewable energy depend on the stability and the dependability of the regulatory framework characterizing the renewable energy investments.…”
Section: Investors Perceptionmentioning
confidence: 99%
“…Integrated Reporting (IR), a new strategy for corporate communication, has received a lot of attention recently as a way to get over these limits (Renato Camodeca, 2018). By strengthening responsibility and stewardship while also improving the quality of the information delivered to stakeholders, IR might meet their needs (Ciubotariu et al, 2021). IR encourages a more unified, succinct, and effective corporate reporting strategy and improves resource allocation in the decision-making process, demonstrating how firms can build value over time (Aceituno, 2013).…”
Section: Introductionmentioning
confidence: 99%